1995
DOI: 10.1093/heapol/10.2.164
|View full text |Cite
|
Sign up to set email alerts
|

User charges in government health facilities in Kenya: effect on attendance and revenue

Abstract: In this paper we study demand effects of user charges in a district health care system using cross-sectional data from household and facility surveys. The effects are examined in public as well as in private health facilities. We also look briefly at the impact of fees on revenue and service quality in government facilities. During the period of cost-sharing in public clinics, attendance dropped by about 50%. This drop prompted the government to suspend the fees for approximately 20 months. Over the 7 months a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
63
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(65 citation statements)
references
References 0 publications
2
63
0
Order By: Relevance
“…In the early 1990s, the government increased the cost of treatment in its clinics through a reform programme known as cost-sharing (Mwabu et al, 1995) but preventive health services were provided free of charge. The positive coefficient on cost per visit suggests that the increased demand for immunizations at government clinics is a result of substituting prevention for more expensive curative care.…”
Section: Market Inputs: Tetanus Vaccinationmentioning
confidence: 99%
“…In the early 1990s, the government increased the cost of treatment in its clinics through a reform programme known as cost-sharing (Mwabu et al, 1995) but preventive health services were provided free of charge. The positive coefficient on cost per visit suggests that the increased demand for immunizations at government clinics is a result of substituting prevention for more expensive curative care.…”
Section: Market Inputs: Tetanus Vaccinationmentioning
confidence: 99%
“…This is particularly true in developing contexts, like that in which this study's empirical analysis is conducted, in which nominal fees for healthcare are heavily subsidized. Distance to the nearest facility (or alternatively, the presence of a formal-care facility in one's community) is thus a large determinant of healthcare choice in developing countries, through its effects on costs (Gertler, Locay, and Samuelson 1987;Mwabu, Mwanzia, and Liambila 1995;Mwabu 2009). …”
Section: A An Instrument For Healthcare Choicementioning
confidence: 99%
“…Case studies on Uganda, South Africa, Madagascar and Kenya provide evidence of the positive effect of the abolition of user fees on the utilisation of health services (James C. et al, 2005). The abandonment of cost recovery in health led to an increase in service utilisation by 53 per cent in Uganda, 41 per cent in Kenya, and 16 per cent in Madagascar (Burnham et al 2004;Deininger, Mpuga 2004;Fafchamps, Minten 2003;Mwabu et al 1995). A study on South Africa showed that with the introduction of free primary health care the total number of consultations for curative care doubled, while that for preventive services fell due to clinic congestion and reduced consultation times (Wilkinson et.…”
Section: Access To Basic Health Services During the Crisismentioning
confidence: 99%